The “Machine contribution” in the European scene - Jan Peeters (Intereconomics, 1986)
The long-term financing of social security faces considerable problems which give rise to the question whether wages can and should continue to serve as the only assessment basis for social security contributions. The calculation of, at least, the employers' contributions on a broader value added based foundation seems to offer a plausible alternative: human labour is being replaced more and more by technology: its value added could be used for financing social security. What would be the economic effects of such a “machine contribution” on employment, competitiveness and growth?
Keywords: 330; Social policy